A comparative analysis of the assessment results of the competence of technical experts by methods of analytic hierarchy process and with using the Rasch model - Velychko, Oleh; Gordiyenko, Tetyana (Eastern-European Journal of Enterprise Technologies, 2018)
Known scales (criteria) for assessing the competence of experts in the field of technical regulation using the method of analytical hierarchy process (AHP) and Rasch model are investigated. The main features of constructing the mathematical Rash model are presented. The results of the analysis of scales for assessing the competence of experts in the field of technical regulation on a specific example of questioned specialists in measurement of time and frequency were considered. The results were processed using the specialized software “Competence MAI 1.1” (Ukraine) and MINISTEP 4.0.1 (USA). A comparative analysis of the results was carried out in order to determine the effectiveness of the assessment scales. The obtained results showed the possibility of applying the Rasch model for the analysis of the scale of expert assessment in the field of technical regulation. The analysis of the results obtained on the multidimensional Rasch model showed that the chosen criteria scale for experts corresponds to the requirements set by the Rash model. The obtained measurement data for this model allow you to calculate the established statistics for both the criteria and for the evaluated experts. A comparative analysis of the results obtained with the use of AHP and Rasch model showed convergence, suitability and correlation of the obtained values for experts. Only two out of twenty one (9.5 %) evaluated experts have data that are unsuitable for the analysis by the Rasch model, which indicates a low level of competence. AHP to a lesser extent allows for the consideration of less competent experts than with the use of the Rash model. This is evidenced by a lower coefficient of competence for the AHP than in the application of the Rasch model. AHP and Rasch model should be used in various fields of activity as a useful tool for comparative assessment of the competence of technical experts on the basis of objective data according to established criteria.